Blood, bone and brain nocardiosis infection in an HIV-infected man - Muhammad Yazli Yuhana (JKKI (Jurnal Kedokteran dan Kesehatan Indonesia), 2016)
Disseminated nocardiosis is a rare and complicated opportunistic bacterial infection with propensity of delay in establishing the correct diagnosis and high frequency for misdiagnosis and due to the non-specific clinical presentation and the inherent difficulty in cultivating the organism. The infection is caused by gram-positive aerobic actinomycetes in the genus Nocardia. A definitive diagnosis requires the isolation and identification by Gram stain and modified acid-fast stain from a clinical specimen. Treatment heavily relies on species and susceptibility testing. There is a real paucity of prospective studies in nocardiosis infection, resulted in severely limited understanding of its diagnosis and treatment among the medical community. We report a clinical case of a 42-year old HIV-infected Burmese man with culture proven Nocardia infection.